Increased Level of Lactate Dehydrogenase Correlates with Disease Growth in Algerian Children with Lymphoma - A Galleze; R Raache; N Cherif; A Eddaïkra; M Belhani; A Bensenouci; C Touil-Boukoffa; M CAttal N Abbadi (Journal of Hematology and Oncology Research, 2017)
Objective: This study aimed to evaluate the relation of Lactate dehydrogenase (LDH) levels with stage of the disease and it role in monitoring tumor response to therapy in lymphoma patients. Methods. LDH levels were evaluated on 65 diagnosed Algerian children and compared to healthy control. Results: Our results revealed that LDH levels were significantly higher in untreated children with both hodgkin’s and non hodgkin’s lymphomas compared to control. Moreover, it was observed that the higher is the stage of disease, the more serum LDH level will be. However, there was a significant fall in serum LDH activity by completion of the chemotherapeutic courses. Conclusion: LDH plays an important role in tumor initiation and maintenance. The elevated serum LDH may reflect, release of the enzyme from malignant cells and suggest that they may reflect tumor burden and therefore correlate with disease progression.
Keywords: Lactate dehydrogenase (LDH)